Filipino single aged adults' support systems from nursing homes - Anteg, Elma Marie G.; Cruz, Edlynne M.
This was an exploratory study that explored the profile, socioeconomic and personal circumstances, past experiences and changes and behavioral patterns of Filipino Single Aged Adults SAAs living in nursing homes in relation to the different kinds of support systems they receive namely 1 Tangible Support 2 Belonging Support 3 Appraisal Support and 4 Self Esteem Support. It also focused on identifying how the circumstances, past experiences, as well as changes in behavioral patterns, are related to the different types of support they receive. Using a qualitative method of indepth interview, the researchers gathered insights from the SAAs who are 60 years old and above. In terms of circumstances, majority of the respondents made a personal decision to reside in the nursing homes where most of them are working professionals prior to their nursing home admission. While there are notable differences in the perceived Appraisal and Self esteem Support of the SAAs, results reported that respondents receive both Tangible and Belonging Support. Another type of support that emerged from the gathered data was Spiritual Support. With respect to the support systems, there were differences in the changes and behavioral patterns of the respondents are brought about by their socioeconomic and personal circumstances and past experiences. The theory and concepts of Urie Bronfenbrenner's Ecological Systems Theory supported the changes and behavioral patterns of the SAAs to provide basis on their experiences. Moreover, since the study focused on non-governmental organizations, it is recommended that publicly funded institutions be explored to account for more insights on the programs of the SAAs in nursing homes.